Motivation-related predictors of physical activity engagement and vitality in rheumatoid arthritis patients - Yu, C.; Rouse, P.; Van Zanten, J.; Metsios, G.; Ntoumanis, Nikos; Kitas, G.; Duda, J. (2015)
This study tests the Basic Psychological Needs Theory (within the Self-determination framework), in relation to the prediction of physical activity and well-being among rheumatoid arthritis patients. Motivation regulations for physical activity were also considered in the process model. A total of 207 patients (150 females, mean age = 58 ± 11 years) completed a questionnaire pack and structural equation modelling was used to test expected relationships. Autonomy support provided by important other(s) regarding physical activity positively predicted rheumatoid arthritis patients’ need satisfaction which positively related to autonomous reasons for physical activity participation. Autonomous motivation positively predicted reported physical activity participation levels and feelings of vitality.